2018
DOI: 10.1186/s13000-018-0712-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of PD-L1 expression and CD8+ T cell infiltration in pulmonary neuroendocrine tumors

Abstract: BackgroundRecent research supports a significant role of immune checkpoint inhibitors in the treatment of solid tumors. However, relevant reports for programmed death-ligand 1 (PD-L1) and CD8+ tumor-infiltrating lymphocytes (TILs) in pulmonary neuroendocrine tumors (PNETs) have not been fully studied. Therefore, we investigated PNETs for the expression of PD-L1 and infiltration by CD8+ TILs as well as the prognostic value of both factors.MethodsIn total, 159 specimens of PNETs (35 TC, 2 AC, 28 LCNEC, 94 SCLC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 27 publications
(24 reference statements)
10
43
0
2
Order By: Relevance
“…Furthermore, more than half of the patients who presented with locally extended disease at diagnoses showed PD-L1 immunoreactivity, compared with only a quarter of the patients with locally confined or extended disease. Although only a limited number of NET G3 were included in our study, our data therefore confirm others who demonstrated PD-L1 expression mainly on TC of poorly rather than of well-differentiated NENs (49, 50) or who even exclusively detected PD-L1 expression in GEP-NEC (51). These results indicate, that the more aggressive the tumor, the higher the expression of PD-L1.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, more than half of the patients who presented with locally extended disease at diagnoses showed PD-L1 immunoreactivity, compared with only a quarter of the patients with locally confined or extended disease. Although only a limited number of NET G3 were included in our study, our data therefore confirm others who demonstrated PD-L1 expression mainly on TC of poorly rather than of well-differentiated NENs (49, 50) or who even exclusively detected PD-L1 expression in GEP-NEC (51). These results indicate, that the more aggressive the tumor, the higher the expression of PD-L1.…”
Section: Discussionsupporting
confidence: 90%
“…First, we noticed that PCs, especially TCs, can express PD-L1. To the best of our knowledge, only four studies on PD-L1 expression in PCs have been published earlier (16, 18, 20, 21). In all studies, PCs were pooled with LCNEC and SCLC, and patient numbers were relatively low, ranging from 22 to 57.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the expression of PD-1 and PD-L1 in SCLC but reports on PC tumors are rare and have involved only a limited number of patients (16, 17, 18, 19, 20, 21). In addition, in most studies PCs have been merged with high-grade LCNEC and SCLC which behave much more aggressively.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 expression in >1% of tumour cells is present in only a minority (~20%) of SCLC specimens [5][6][7][8] . Retrospective studies of samples obtained from patients with SCLC before the introduction of ICIs have demonstrated a better prognosis in those with high counts of tumour-infiltrating lymphocytes (TILs) [17][18][19][20] . Each retrospective analysis was performed in samples from a slightly different patient population and revealed different associations.…”
Section: Immunobiology and Subtypesmentioning
confidence: 99%
“…Each retrospective analysis was performed in samples from a slightly different patient population and revealed different associations. The presence of CD8 + stromal TILs was associated with superior progression-free survival (PFS) and overall survival (OS) (both P < 0.05) in patients with pulmonary neuroendocrine tumours of any histology, 59.1% of whom had SCLC 18 . The presence of suppressive FOXP3 + regulatory T cells was found to be associated with a better prognosis in patients with limited-stage (stage I-III) SCLC (LS-SCLC) (HR 0.37, 95% CI 0.17-0.81; P = 0.013) 17 .…”
Section: Immunobiology and Subtypesmentioning
confidence: 99%